Frontier swashbuckler : the life and legend of John Smith T - Steward, Dick, 1942- (Missouri biography series., 2000)
"Few frontiersmen in the late eighteenth century and early nineteenth century epitomized the reckless energies of the West and the lust for adventure as did John Smith T - pioneer, gunfighter, entrepreneur, militia colonel, miner, judge, and folk hero. In this biography, Dick Steward describes Smith T's remarkable career in the wilds of Missouri and his armed raids to gain land from Indians, Spaniards, and others." "Born into the fifth generation of Virginia gentry, young Smith first made his name on the Tennessee frontier. It was there that he added the "T" to his name to distinguish his land titles and other enterprises from those of the hosts of other John Smiths." "In 1797, Smith T moved to Missouri, then a Spanish territory, and sought to gain control of its lead-mining district by displacing the most powerful American in the region, Moses Austin. He acquired such public positions as judge of the court of common pleas, commissioner of weights and levies, and lieutenant colonel of the militia, which enabled him to mount a spirited assault on Austin's virtual monopoly of the lead mines. Although neither side emerged a winner from that ten-year-old conflict, it was during this period that Smith T's fame as a gunfighter and duelist spread across the West. Known as the most dangerous man in Missouri, he was said to have killed fourteen men in duels." "Smith T was also recognized by many for his good works. He donated land for churches and schools and was generous to the poor and downtrodden. He epitomized the opening of the West, helping to build towns, roads, and canals and organizing trading expeditions on the Santa Fe Trail."--Jacket